Differential susceptibility in a developmental perspective: DRD4 and maternal sensitivity predicting externalizing behavior. Issue 1 (23rd September 2014) - Windhorst, Dafna A.; Mileva‐Seitz, Viara R.; Linting, Mariëlle; Hofman, Albert; Jaddoe, Vincent W.V.; Verhulst, Frank C.; Tiemeier, Henning; van IJzendoorn, Marinus H.; Bakermans‐Kranenburg, Marian J.
ABSTRACT This study is the first to investigate the longitudinal effects of gene–environment interplay between DRD4 genotype and maternal sensitivity on child externalizing behavior. Multiple measures of maternal sensitivity (14, 36, and 48 months) and externalizing behavior (18 months, 36 months, and 5 years) were assessed in a large cohort study (N = 548). Early maternal insensitivity (14 months) was associated with early externalizing behavior (18 months) in a for better and for worse manner, but only in children with at least one DRD4 7‐repeat, consistent with a differential susceptibility model. Later insensitivity (48 months) predicted externalizing behavior at age 5 independent of DRD4 genotype. A structural equation model including all measures across time supported the differential susceptibility model: The overall effect of early maternal sensitivity on later externalizing behavior was significant only for children with a DRD4 7‐repeat allele. The results highlight the importance of studying gene–environment interactions across development. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 57: 35–49, 2015.